The role of the proteasome-associated protein Ecm29 in quality control of the proteasome - De La Mota-Peynado, Alina M. (Kansas State University, 2014)
The ubiquitin-proteasome pathway is the major pathway of selective protein degradation in the cell. Disruption of this pathway affects cellular protein homeostasis and contributes to diseases like cancer, and neurodegeneration. The end point of this pathway is the proteasome, a complex protease formed by 66 polypeptides. Structurally, it can be subdivided into the Core Particle (CP) and the Regulatory Particle (RP). The CP harbors the proteolytic sites, whereas, the RP contains six orthologous AAA-ATPases, the Rpt proteins. These Rpt’s are essential for proteasome function and are at the interface between RP and CP. The work in this thesis focuses on the Rpt subunit Rpt5 from yeast. The C-terminal tail of Rpt5 has been shown to contribute to the binding with the CP. However, our study showed it is also essential for the interaction with Nas2, one of nine proteasome-specific chaperones. Thus, Nas2 might function as a regulator of the Rpt5-CP interaction. Further analyses suggested that Nas2 has an additional function in assembly, and that mutating the tail of Rpt5 results in increased binding of the proteasome-associated protein Ecm29 to the proteasome. We showed that Ecm29 binds Rpt5 directly, thereby inducing a closed conformation of the CP substrate entry channel, and inhibiting proteasomal ATPase activity. Consistent with these activities, several proteasome mutant strains showed Ecm29-dependent accumulation of unstable substrates. Thus, Ecm29 is an inhibitor of the proteasome in vivo and in vitro. Interestingly, besides the Rpt5 mutants, several other proteasome mutants show increased levels of Ecm29, suggesting Ecm29 has a role in quality control. Consistent with this, we observed that Ecm29 associates preferably with specific mutants and nucleotide-depleted proteasomes. Based on our data we propose a model, where early in assembly Nas2 binds to the Rpt5 tail inhibiting the Rpt5-CP interaction directly. Later in assembly Ecm29 performs a quality control function, where it recognizes and remains bound to defective proteasomes. By inhibiting these proteasomes Ecm29 prevents the aberrant degradation of proteins.
Keywords: Proteasome assembly; Ecm29; Molecular chaperones; Biology (0306)